Identifikasi Suara Pada Sistem Presensi Karyawan Dengan Metode Ekstraksi MFCC - Widodo, Yuwono Fitri; Sunardi, Sunardi; Fadlil, Adbul (STIKOM Tunas Bangsa Pematangsiantar, 2019)
Biometrics is the study of patterns of characteristics to recognize or identify humans based on one or more parts of the human body, both chemical, physical, and behavioral characteristics, such as faces, fingerprints, sounds, hand geometry, or iris. Nowadays technology has developed using sound to be used as an application that facilitates humans. Voice identification process is very necessary to know the accuracy of the sound based on the characteristics possessed, because some humans have similarities in saying. In this study aims to determine the sound pattern based on speech. The method used for voice identification using the Mel-Frequency Cepstral Coefficients (MFCC) feature extraction method, is a feature extraction method that approaches the human hearing system and is able to recognize speech patterns.